Reflecting on emotional political ecoloiges. - Heras, María; Singleton, Benedict; Kotsila, Panagiota (Soft Power, 2017)
Three researchers share their thoughts about a roundtable discussion on Emotional Political Ecologies during the ENTITLE Undisciplined Environments Conference, held in Stockholm from 20 to 24 March 2016.